The Effect of Financial Performance on The Tobin's Q Value of Company Investment - Listiadi, Agung (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to provide To explain the impact of financial performance, corporate social responsibility and good corporate governance on firm value. Companies that sell their shares to the public by going public must have a good picture. A good picture is necessary to gain the trust of investors. Companies in an effort to gain the trust of investors will provide reliable information. This information describes the character of the company, especially regarding financial performance. This study used a descriptive associative quantitative research method. To determine the effect of firm value used regression analysis techniques. From the research results there is a significant influence between financial performance on firm value, this occurs due to the Efficient Market Semi Strong Hypothesis. Based on the results of the discussion that has been put forward, the conclusion in this study is simultaneous that there is a significant influence between financial performance, corporate social responsibility, good corporate governance on firm value ratio expressed by the Tobin's Q, when investing in companies that are included in the LQ-45 stock indexer in Indonesia, list namely the best stock rating index in Indonesia.  The limitation in this study is that the measurement for company value is to use Tobin's Q, which is calculated based on the market value/price of a company divided by the company's asset value. Measurement of company value is carried out for a years. The results of this research for the industrial world can be used as a source of information about efforts in implementing financial performance on firm value with CSR disclosure and good corporate governance (GCG) as intervening variables. And it is hoped that it can provide useful information for readers, especially investors, potential investors, and capital market authority bodies regarding the relevance of CSR information disclosure and good corporate governance in company annual reports with firm value and financial performance.